Explaining the Dynamic Hedging Policy of the Duterte Administration Amid the Sino-US Rivalry - Fauzan Rizki, Muhammad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This article explains the dynamics of Duterte’s foreign policy in responding to geopolitical uncertainty in Southeast Asia. The Philippines’ geopolitical alignment toward China shifted during his administration, marking a significant break in its foreign policy history. The Duterte administration has also been distancing the Philippines from the United States. As a result, the Philippines' foreign policy orientation began to view its relations with the two powers more pragmatically. Using hedging as an analytical framework and a qualitative-deductive method of analysis, this article argues that the Duterte administration adopted a hedging-oriented foreign policy shaped by both the structural climate and domestic socio-bureaucratic considerations. Furthermore, his approach reflected strong policy dynamism, marked by flexible and anticipatory shifts in alignment during the latter half of his administration in response to perceived risks and opportunities.